¿TESTIMONIOS DE UN DESPOJO? DESARROLLO TURÍSTICO EN GUANACASTE Y SUS IMPACTOS A NIVEL SOCIAL Y AMBIENTAL, 1990-2016 - Blanco Obando, Edgar (2017)
This article identifies the main social and environmental results derived from tourism development in Guanacaste’s coasts, through the analysis of theoretical, scientific and statistical data, as well as information collected through interviews with local activists. It is considered that tourism development is guilty of intensive appropriation of nature and overexploitation of the aquifers that supply local communities, as well, the emergence of social movements against developers and government, to control access to environmental resources considered basics to subsistence.